Overweight, Obesity and Nutritional Anemia in the Adult Woman - Pajuelo Ramírez, Jaime (2000)
OBJECTIVES: To determine the prevalence of nutritional anemia in women with overweight and obesity and the behaviour of deposit ratios. MATERIAL AND METHODS: One hundred seventy nine women, 20 to 59 years of age and are attended at Dos de Mayo Hospital for overweight and obesity, were studied. All were weighted, heighted and their arm perimeter (AP) and skinfold triceps (ST) measured, as well as the muscular and fat areas (FA). At random 74 women were selected for hemoglobin study. Overweight and obesity I and II were diagnosed by means of Quetelet Index (QI). Anemia was determined by HB below 12 gr/dL. RESULTS: Anthropometric indicators raise in accordance with QI increase, the same does not occur with HB values. QI presented by overweight and obese women as shows a statistically significant correlation with weight, AP,ST and FA; the HB has a very low correlation and significance. Anemics and non-anemics, have no statistical difference. Twenty eight percent of overweight women and 24% with obesity have anemia. CONCLUSIONS: We found coexistence of nutritional deficiency with nutritional excess disease. Since nutritional anemia is an endemic disease in Peru, it is recommended to dose HB in all patients who request assistance for overweight and obesity.